Determining waste generation factors in Klang Valley refurbishment projects / Chai Kok Liong - Chai, Kok Liong (2016)
Construction wastes become serious environmental problems in many countries. In Malaysian construction industry, the waste generation is so significance to the cost of construction project. Waste can be produced because of variety factors. Within the lifecycle of buildings, waste could be generated in the process of during the construction and demolition phases. This will directly affect to the cost and it will become a burden to clients due to bear the costs of waste eventually. The aim of this study is to find out the effectiveness of waste implementation methods in order to reduce the actual construction cost. The factors that cause waste generation will be study in this research. Research in waste implementations will be study in this research as well in order to provide greater scenario of waste minimisation in Malaysia construction industry. After that, the significance of waste implementations will be identified from data analysis. Questionnaires will be prepared and distribute to the construction sector people to identify the real scenario of waste minimisation in construction industry of Malaysia. The methodologies used are by survey. Through survey and analysis processes, the objectives of this research will be discovered and then the researcher could able to recommend and suggest advices on waste minimisation. The recommendation listed out and discussed will enhance the waste minimization for the construction industry and hopefully the reader of this research could realise the importance of waste minimization.